(untitled) (Research, Society and Development, 2021)
The objective was to identify the perception of the landless population about access to health services and health care. This is a descriptive exploratory study, of a qualitative nature. The data collection consisted of an individual semi-structured interview with 11 subjects, between campers and settlers from the Movement of Landless Rural Workers (MST) located in the state of Rio Grande do Norte, in the Brazilian Northeast. The treatment of the data occurred through the technique of content analysis in which there was the delimitation of two categories: Life in the MST and Health Care. The daily life portrays precarious housing and work conditions, family farming and expectations of improvements with land tenure. There is difficulty in access, health actions are restricted and punctual, focused on the hegemonic model. It highlights the importance of improving access to services, with participatory management, planning intersectoral actions linked to the other policies of the Ministry of Health (MS) in order to promote health.